Regulation and Practice of Salam and Istishna Contracts in The Islamic Banking System in Indonesia - Amalia, Eliza; Rahma, Ely; Aulia, Mutifah; Qamariah, Zaitun (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This study analyzes the regulation and practice of akad salam and istishna in the Sharia banking system in Indonesia. By paying attention to the existing regulatory framework, this article examines the practical implementation of akad salam and istishna by Sharia banks in Indonesia as well as the challenges faced in the application of the contract. The results of the analysis highlight the importance of a deep understanding of sharia principles in the development of appropriate sharia banking products and services. Keywords: Akad Salam, Istishna, Sharia Banking, Regulation, Practice.